Bahan Tambahan dalam Sediaan Tablet: Review - Pratiwi, Puspa Dwi; Citrariana, Shesanthi; Gemantari, Baiq Maylinda (Universitas Hamzanwadi, 2023)
Tablets are solid pharmaceutical dosage form without or with suitable excipients by press or compression manufacturing process. The excipient chosen can influence the product performance (physical properties and stability) and bioavailability. All excipients must be optimally selected to get the optimal formula of tablet dosage form. This article review aims to overview of excipient in tablet dosage form and their role in formulating tablet dosage form. this review article was written based on literature studies from electronic databases such as PubMed, ScienceDirect, and Google Scholar which contain related information using keyword in Indonesian or English use article published in 2013-2023. excipients in tablet dosage form are fillers or diluents, disintegrants, lubricants, preservatives, flavors, sweeteners, coloring, and coating agents. These excipients added to tablet dosage form to facilitating the process of manufacture tablet dosage form, increasing stability and effectiveness of active pharmaceutical ingredients in tablet. The conclusion of this review, there are many classification of tablet excipients which is different function to get compendial requirements of tablet dosage form.